The Impact of Sleep on Athletes Performance and Injury Risk: A Narrative Review - Rygielski, Artur; Melnyk, Bohdan; Latour, Emilia; Latour, Marianna; Judek, Roksana; Kowalczyk, Zuzanna; Stanek, Aleksandra; Płudowska, Katarzyna (Quality in Sport, 2024)
Introduction and purpose Sleep is a critical component of an athlete’s health, significantly influencing injury risk, performance, and recovery. It plays a vital role in the healing process, contributing to growth, repair, regeneration, and immunity. Current literature suggests that sleep quality impacts various aspects of athletic performance, including physical and cognitive abilities, recovery, injury risk, and mental well-being. This narrative review aims to explore the impact of sleep on the musculoskeletal system of athletes, particularly focusing on injury risk, performance, and recovery. It seeks to synthesize existing research to highlight the importance of sleep quality and duration in maintaining and enhancing athletic performance. Description of the state of knowledge The findings indicate that less than 7 hours of sleep is consistently associated with an increased risk of musculoskeletal injury, with athletes experiencing a 1.7 times higher risk if this sleep pattern persists for at least 14 days. Some studies also highlight that athletes obtaining fewer than 6 hours of sleep per day show significant performance declines and higher injury rates. Summary While evidence clearly links certain sleep behaviors to increased musculoskeletal injury and pain, it is crucial to consider sleep as one aspect of an athlete’s overall health and well-being. Adequate sleep is essential for optimal athletic performance, injury prevention, and recovery. Tailored sleep strategies should be integrated into training and recovery protocols to enhance the overall health and performance of athletes.